Collaboration a potential history of photography - Azulai, Ariʾelah 1962-; Ewald, Wendy 1951-; Meiselas, Susan 1948-; Raiford, Leigh ca. 20./21.Jh; Wexler, Laura (Thames & Hudson, 2023)
Collaboration presents a groundbreaking and multifaceted history of photography which explores photography through the lens of collaboration, challenging the dominant narratives around photographic history and authorship. In a vast, collaborative effort led by five of the great thinkers and practitioners in photography that includes more than 550 photographs and over 80 text contributors, this book breaks apart photography’s ‘single creator’ tradition by bringing to light tangible traces of collaboration – the various relationships, exchanges and interactions which occur between all participants in the event of photography. This book offers the keys to understanding and decoding the complex politics of seeing. The conditions of collaboration in photography are explored through over 100 photography projects, divided into eight thematic chapters. The photographs from each project are presented non-hierarchically alongside quotes, testimonies, and short texts by guest contributors. These networks of texts and images provide perspective on a vast array of photographic themes, from Araki’s provocative portraits of women to archival files from the Spanish Civil War. Collaboration is not an ultimate account of what photography is, does, or means. Rather, the book is an inspiration for teaching and an open invitation to scholars, activists, photographers and others to practice always with and alongside others and participate actively in this engagement and enquiry
Includes bibliographical references and index
Keywords: Fotografie; Photography / History; Photographers / History; Photographie - Histoire; Photographes - Histoire; Photography / (OCoLC)fst01061714; History / (OCoLC)fst01411628